Complement in PNH and other hemolytic anaemias 1 - Luzzatto, Lucio (Henry Stewart Talks, 2017)
Overview of the human complement system, Coagulation cascade and complement cascade, The complement and hemolytic anaemias, Anaemias and intravascular hemolysis, Complement-mediated hemolysis, Possible role of complement in malaria, Genetically defective regulation (inherited), Role of complement in different conditions (Shiga toxin & aHUS)